In House Oxygen Persufflation of Cold Stored Livers Versus Simple Cold Storage in Extended Criteria Liver Grafts: 5-year Results of a Randomized Controlled Clinical Trial. (July 2018) - Gallinat, Anja; Hoyer, Dieter DP; Klein, Christian; Benkoe, Tamas; Sotiropoulos, Georgios; Treckmann, Jürgen; Paul, Andreas; Minor, Thomas
Abstract : Two hours of end-ischemic oxygen persufflation of cold stored porcine livers regenerates cellular energy dependent pathways and improves survival after transplantation. The present trial evaluated oxygen persufflation as adjunct in clinical liver preservation. Patients and Methods: Between 1/11 and 12/13 a total of n=116 adult patients (age: 54(23-68) years, M/F: 70/46), were enrolled in this prospective randomized study. Grafts were randomized to either retrograde O2-persufflation for ≥ 2 hours (O2) or mere cold storage (control). Only liver grafts from donors ≥55 years and/or grafts allocated as rescue offers were included. Primary endpoint was peak-AST level till post-op. day 3. Standard parameters including EAD, post-Op complications and 5 year graft- and patient survival were evaluated as secondary endpoints. Data were analyzed by…. Results: Both study groups were comparable except for a longer ICU stay (4 vs. 3 days) of the donors and a higher recipient age (57 vs. 52 years) in the O2-group. S-TNF-α and TNF gene expression in liver tissue 1h after reperfusion was reduced in the O2 group (p<0.05). Median peak-AST values did not differ between the groups (O2: 580 U/l, control: 699 U/l). 2 patients (1.7%) were re-transplanted for PNF/hepatic artery thrombosis. Five year patient- and graft survival was similar (O2 vs. control: 74% vs. 66% and 89% vs. 82%, p=n.s.). On multivariate Analysis 5 year patient survival was significantly improved in livers within macrosteatosis, donor age > 70years and when cold ischemia time was prolonged when O2 persufflation was applied. Conclusions: Oxygen persufflation can be considered as a safe and easy alternative to simple cold storage or machine perfusion in predamaged livers.